Studi Sektor Keuangan terhadap Kualitas Lingkungan di ASEAN-5 - Adiet Try Waluyo; Lukman Hakim; Siti Aisyah Tri Rahayu (School of Postgraduate Studies, Diponegoro Univer, 2023)
This research to critically review the influence of the dimensions of financial sector development on carbon dioxide emissions in ASEAN-5 developing countries, namely Indonesia, Malaysia, Thailand, the Philippines. The development cycle of the financial sector can increase and decrease environmental quality. We use the Panel Least Square (PLS) model to analyze the dynamics of the financial sector on environmental quality in annual data for 1983 - 2020 in five ASEAN-5 countries. The results of this study found that economic growth, foreign direct investment, and financial development have a positive effect on carbon dioxide emissions. However, interest rates have a negative effect on carbon dioxide emissions. Moreover, this study found that the development of the financial sector has a negative effect on environmental quality. This means that every increase in economic growth, FDI, and financial development has an effect on a decrease in environmental quality. Therefore, this finding is important for policy makers in ASEAN-5 countries to reduce dependence on investment that is not environmentally friendly as a factor of production and increase green financing in every activity in the financial sector.